Zero Waste Water Day: Educational Strategies to Foster Awareness of Clean Water Among Students - Ratna Intan Cahayanik; Puji Winarti; Ridha Sarwono (Universitas Pancasakti Tegal, 2025)
This research aims to foster awareness of clean water among students through the Zero Waste Water Day Program. The method used in this research is quantitative descriptive with a One Group Pretest Posttest Design. The research subjects are the 25 students of class VB at SDN Kalongan 02. The data collection technique used pretest and posttest questionnaires. This program uses a contextual and participatory approach, thereby directly involving the students. The implementation of the Zero Waste Water Day Program received a positive response from the students; they showed high curiosity, enthusiasm, and full spirit. Based on research data, students who have participated in the Zero Waste Water Day Program have shown an increase in awareness of clean water, and they are increasingly understanding the importance of clean water for daily needs. The N-Gain test result of 0.7178 indicates an increase in the high category. Thus, the research results indicate that the Zero Waste Water Day Program is effective in fostering awareness of clean water among students